Diplomatic Relations of the Khanate of Kokand with China and the Countries of the Muslim East - Abdurahmonov, Zuhriddin (Researchparks Publishing, 2023)
This article discusses the scientific researches on the diplomatic relations of the Khanate of Kokand with the neighboring Muslim countries, in particular, Turkey, Iran, as well as China and the Russian Empire.